1995
DOI: 10.1677/joe.0.1470139
|View full text |Cite
|
Sign up to set email alerts
|

Levels of pro-opiomelanocortin and prolactin mRNA in the fetal sheep pituitary following hypoxaemia and glucocorticoid treatment in late gestation

Abstract: It is well established that corticotrophin-releasing hormone and vasopressin can induce both synthesis and release of ACTH from the ovine pituitary gland, and that glucocorticoids can inhibit these responses. Changes in the abundance, localization and distribution of pro-opiomelanocortin (POMC) mRNA and prolactin (PRL) mRNA in the ovine fetal pituitary were examined by in situ hybridization following hypoxaemia applied in the presence or absence of concomitant cortisol in late gestation (day 135). Fetuses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…Hypoxemia-induced increases in fetal plasma concentrations of ACTH and cortisol, appropriate for the degree of hypoxemia and the gestational age of the fetus (10,30 -33), were prevented by maternal dexamethasone, consistent with previous studies in fetal sheep (10,34,35). Both direct fetal i.v.…”
Section: Dexamethasone and The Materno-fetal Hpa Axissupporting
confidence: 88%
“…Hypoxemia-induced increases in fetal plasma concentrations of ACTH and cortisol, appropriate for the degree of hypoxemia and the gestational age of the fetus (10,30 -33), were prevented by maternal dexamethasone, consistent with previous studies in fetal sheep (10,34,35). Both direct fetal i.v.…”
Section: Dexamethasone and The Materno-fetal Hpa Axissupporting
confidence: 88%
“…It appears that the decrease in 11␤HSD-2 mRNA levels in response to cortisol is not through an indirect action of cortisol at the fetal pituitary, as there was no change in circulating ACTH in response to the intrafetal cortisol infusion. It has been reported that intrafetal infusion of cortisol before the prepartum activation of the fetal pituitaryadrenal axis inhibits fetal ACTH responses to stimulation by corticotrophin releasing factor [17] or acute stressors such as hypoxemia [18], but does not suppress basal ACTH secretion or steady-state expression of the ACTH precursor, proopiomelanocortin (POMC), in the fetal pituitary [19]. In contrast, cortisol infusion after 140 days gestation suppresses basal and stimulated ACTH concentrations [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Brains were removed, weighed, and rapidly frozen on dry ice and stored at −80 °C until molecular analysis. The method for in situ hybridisation has been described in detail previously (26). Coronal cyrosections (12 µm) were mounted onto (poly)‐L‐lysine (Sigma Chemical, St Louis, MO, USA)‐coated slides, dried, and postfixed with 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%